Pengaruh Modal Kerja, Solvabilitas Dan Likuiditas Terhadap Nilai Perusahaan Pada Perusahaan Sektor Transportasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2022 - Ammalia, Dian; Tambunan, Saribulan (CV. ITTC INDONESIA, 2025)
The value of the company is reflected in the stock market value, where the increase in stock prices will increase investor interest in the company so that the higher the prosperity obtained by investors, firm value plays a role in making business decisions, because it can be a consideration in raising capital, purchasing assets, or determining the company's dividend policy. The purpose of this study is to determine the effect of working capital, solvency and liquidity on company value in transportation sector companies listed on the Indonesia Stock Exchange in 2019-2022. The research design used is an associative approach. The population in this study were 23 transportation sector companies listed on the Indonesia Stock Exchange in 2019-2022 with a sampling technique using purposive sampling, so that the research sample was 18 transportation sector companies listed on the Indonesia Stock Exchange in 2019-2022. In this study, the type of data used is quantitative data. The data source used in this study was obtained from the Indonesia Stock Exchange (IDX) website. The data analysis method uses multiple linear regression analysis with SPSS.25. Based on the results of the t-test that has been carried out, it can be concluded that working capital has a positive and significant effect on company value, solvency has a positive and significant effect on company value and liquidity has a positive and significant effect on company value. Based on the results of the f-test, it is concluded that working capital, solvency and liquidity have a simultaneous effect on the company value of companies in the transportation sector listed on the Indonesia Stock Exchange in 2019-2022.